Internet-Based Short Course for Teacher Training College - Sazali, Saidin (2003)
The momentous transition from industrial age to knowledge age delivers a new challenge for the nation as a whole as we negotiate the difficult to educate people. Today we must understand systems in diverse contexts, collaborate locally and global around the globe using new tools like the Internet. Many educators have recognized the potential of using the Internet for instruction. Although many Internet technologies such as e-mail, listservs, ftp and video conferencing can be used to assist with teaching, but the World Wide Web remains the most popular medium. It provides a user friendly front end and easy access to text, graphics, audio and video materials that may be used in a common and consistent format. One of the most powerful elements of using the Web for teaching is the ability to engage learners in an interactive format. Most education Web sites provide basic course information such as syllabus, schedule, announcements and reading lists. In Malaysia, the function of the education institution must be broadening to accommodate the big challenge of the technology used in the education milieu. For this reason, Maktab Perguruan Perlis, Perlis, one of the Teacher Training Colleges, proposed a Internet-Based Short Course System that will handles online short courses where teachers can access them anywhere and anytime. This study is proposed to develop a database-driven of an Internet-based short course to handle Data Communication and Networking for teachers to enhance their skill. Therefore the aim is to make learning more accessible, interactive, meaningful, student-centered, support collaboration and flexible. Upon completing the project, the Database Design Methodology and Web Development Methodology are used to build the system. Rapid Software Prototyping Methodology technique is used to develop a prototype. The MySQL Database, PHP, JavaScript and Apache web server are used to implement the system. The system model is a reference model to the institution’s Internet-based short course system. During the development of the system, some problems and limitations were discovered and discussed. Finally some recommendations are made to overcome the limitations for the future enhancement and future work of this project.